0368 Sleep Health Among Transgender Women of Color in New York City: Preliminary Analyses of the Turnnt Study. (27th May 2020) - Duncan, D; Schneider, J; Radix, A; Harry-Hernandez, S; Callander, D
Abstract: Introduction: Little is known about sleep health among transgender and gender diverse populations. Even less is known about sleep among transgender women of color, a population that experiences considerable health disparity. Methods: Interim baseline data were analyzed from the TURNNT (Trying to Understand Relationships, Networks and Neighborhoods among Transgender women of color) Study, an ongoing cohort of 350 HIV-negative transgender women of color in New York City. At baseline, items from the widely-used Pittsburgh Sleep Quality Index (PSQI) were used to measure typical sleep duration and subjective sleep quality. For example, typical sleep duration was measured with the PSQI item, "During the past month, how many hours of actual sleep did you get each night?". Participant responses were analyzed descriptively; the Mann-Whitney U test was used to assess bivariate associations. Results: As of November 2019, there were n=31 participants enrolled in TURNNT. Nearly half of participants earned less than 30, 000 per year (48%) and in the 6 months before participation 61% had experienced food insecurity and 13% reported being unstably housed. Participants reported typically receiving 2-12 hours of sleep per night (median=6 hours). With short sleep defined as <7 hours per night, 55% reported this during the month prior to participation in the study, while 29% of participants rated their overall sleep quality as poor. Typical sleep duration was equivalent among participants with lower or higher incomes (5.5 vs 7 hours, p=0.3), but those who faced food insecurity reported less sleep (5 vs 7 hours, p<0.05) as did those who experienced housing instability (3.5 vs 7 hours, p<0.05). Conclusion: Poor sleep health was common among our sample of transgender women of color, especially among those experiencing food insecurity and housing instability. Future research should examine multi-level correlates of poor sleep health such as network structures and neighborhood environments. Support: The TURNNT (Trying to Understand Relationships, Networks and Neighborhoods among Transgender women of color) Study is funded through grants from the National Institute on Minority Health and Health Disparities (Grant Numbers: R01MD013554 and 3R01MD013554-02S1; Principal Investigator: Dustin T. Duncan, ScD).